CRISPR/Cas9-Mediated Genome Editing and Mutagenesis of EcChi4 in Exopalaemon carinicauda. Issue 11 (1st November 2016) - Gui, Tianshu; Zhang, Jiquan; Song, Fengge; Sun, Yuying; Xie, Shijun; Yu, Kuijie; Xiang, Jianhai
Abstract: The development of the type II clustered regularly interspaced short palindromic repeats (CRISPR) system has resulted in the revolution of genetic engineering, and this technology has been applied in the genome editing of various species. However, there are no reports about target-specific genome editing in shrimp. In this research, we developed a microinjection method for the ridgetail white prawn Exopalaemon carinicauda and successfully applied CRISPR/Cas9 technology to the genome editing of E. carinicauda . Through coinjection of mRNA of Cas9 nuclease and gRNA specialized for E. carinicauda chitinase 4 ( EcChi4 ), shrimps with indel mutations were obtained. Further analysis showed that the mutations could be transmitted to the next generation. This is the first time that site-specific genome editing has been successfully demonstrated in a decapod, and will further contribute to the study of functional genomics in decapods.